Novel rodent models for macular research - Huber, Gesine; Heynen, Severin; Imsand, Coni; Vom Hagen, Franziska; Muehlfriedel, Regine; Tanimoto, Naoyuki; Feng, Yuxi; Hammes, Hans-Peter; Grimm, Christian; Peichl, Leo; Seeliger, Mathias W.; Beck, Susanne C. (PLOS ONE, 2010)
Background Many disabling human retinal disorders involve the central retina, particularly the macula. However, the commonly used rodent models in research, mouse and rat, do not possess a macula. The purpose of this study was to identify small laboratory rodents with a significant central region as potential new models for macular research. Methodology/Principal Findings Gerbillus perpallidus, Meriones unguiculatus and Phodopus campbelli, laboratory rodents less commonly used in retinal research, were subjected to confocal scanning laser ophthalmoscopy (cSLO), fluorescein and indocyanine green angiography, and spectral-domain optical coherence tomography (SD-OCT) using standard equipment (Heidelberg Engineering HRA1 and Spectralis™) adapted to small rodent eyes. The existence of a visual streak-like pattern was assessed on the basis of vascular topography, retinal thickness, and the topography of retinal ganglion cells and cone photoreceptors. All three species examined showed evidence of a significant horizontal streak-like specialization. cSLO angiography and retinal wholemounts revealed that superficial retinal blood vessels typically ramify and narrow into a sparse capillary net at the border of the respective area located dorsal to the optic nerve. Similar to the macular region, there was an absence of larger blood vessels in the streak region. Furthermore, the thickness of the photoreceptor layer and the population density of neurons in the ganglion cell layer were markedly increased in the visual streak region. Conclusions/Significance The retinal specializations of Gerbillus perpallidus, Meriones unguiculatus and Phodopus campbelli resemble features of the primate macula. Hence, the rodents reported here may serve to study aspects of macular development and diseases like age-related macular degeneration and diabetic macular edema, and the preclinical assessment of therapeutic strategies.
Gesehen am 25.04.2023